2014
DOI: 10.1186/1471-2407-14-522
|View full text |Cite
|
Sign up to set email alerts
|

Increased malignancy of oral squamous cell carcinomas (oscc) is associated with macrophage polarization in regional lymph nodes – an immunohistochemical study

Abstract: BackgroundIt is largely accepted that specific immunological parameters in solid malignancies are associated with patient’s prognosis. Recently a correlation of macrophage polarization with histomorphological parameters could also be shown in oral squamous cell carcinoma (oscc). The observed tumor derived peripheral immune tolerance could be associated with the macrophage polarization in regional tumor draining lymph nodes.So far there are no studies analyzing the macrophage polarization in cervical lymph node… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 49 publications
3
53
0
1
Order By: Relevance
“…There is compelling evidence that tumour-associated macrophages (TAMs) have potential involvement in the progression and metastatic spread of OSCC. The most important features associated with their presence in the lesion stroma include facilitation of angiogenesis, tumour cell invasion, augmentation of cell motility, persistent growth, and suppression of anti-tumour responses [913]. The signals involved in communication between tumour cells and macrophages have not yet been completely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…There is compelling evidence that tumour-associated macrophages (TAMs) have potential involvement in the progression and metastatic spread of OSCC. The most important features associated with their presence in the lesion stroma include facilitation of angiogenesis, tumour cell invasion, augmentation of cell motility, persistent growth, and suppression of anti-tumour responses [913]. The signals involved in communication between tumour cells and macrophages have not yet been completely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, soluble CD163 and the presence of CD68 + TAMs at the invasive front of the tumor were independent prognostic factors for overall survival of patients with stage I/II melanoma before definitive surgery [36]. Further, Wehrhan and colleagues revealed that an increased malignancy of oral squamous cell carcinomas is associated with polarization of macrophages to the M2 type in regional lymph nodes [78]. Altogether, these data suggest TAMs as potential biomarkers with prognostic/ predictive relevance and may support the development of novel agents targeting TAMs in combination with RT/RCT.…”
mentioning
confidence: 97%
“…Oberg et al . (2002) showed that poor patient survival correlates with the number of M2 macrophages [22]. …”
Section: Discussionmentioning
confidence: 99%
“…This tumour antigen is then engulfed and concentrated within the TAMs [25]. Direct communication between macrophages and tumour cells is said to prepare the regional lymph nodes for the acceptance and sustenance of metastases [22, 26]. …”
Section: Discussionmentioning
confidence: 99%